P057 Mucosal microbiota adapts to ATF6-induced alterations in host lipid metabolism with prognostic value in colorectal cancer. (21st January 2022) - Bierwirth, S; Sorbie, A; Coleman, O; Reuß, E; Weber, P; Köhler, N; Kacprowski, T; Dunkel, A; Pauling, J; Ecker, J; Baumbach, J; Rosenstiel, P; et al.
Abstract: Background: Colorectal cancer (CRC) is a leading cause of cancer deaths worldwide. The endoplasmic reticulum unfolded protein response (UPR ER ) signal transducer activating transcription factor 6 (ATF6) is a clinically relevant pre-cancerous marker in CRC and colitis-associated CRC. We established the interrelated role of the microbiota and ATF6 signalling as a novel tumor-promoting mechanism in our transgenic mouse model of spontaneous microbiota-dependent ATF6-driven CRC (nATF6 IEC ). Methods: To elucidate the transcriptional program initiated by acute and chronic ATF6 signalling, mRNA sequencing analyses of murine colonic intestinal epithelial cells were performed 4 days or 5 weeks after induction of ATF6, respectively. Germfree (GF) mice served to dissect microbiota contribution to the transcriptional response. CRC patient datasets (TCGA) were used to estimate ATF6 activity and validate ATF6-driven signatures. To investigate the impact of ATF6 signalling on metabolites, untargeted metabolomics of faeces and targeted lipidomics of tissue were performed. Mucosal microbiota was spatially characterised by 16S rRNA profiling at mm resolution along the colonic longitudinal axis. Based on 16S rRNA data, Phylogenetic Investigation of Communities Reconstruction of Unobserved States (PICRUSt2) was used to infer microbiota lipid-specific functional content. Results: We identified an ATF6-UPR core of 368 differentially expressed genes fully activated by acute ATF6 signalling. Functional analysis using KEGG pathways showed that chronic ATF6 signalling predominantly alters UPR-related and metabolic pathways, with 22% of metabolic pathway genes classified as lipid metabolism. GF mice confirmed that the microbiota enhances ATF6-induced metabolic changes. Kaplan-Meier analyses significantly associate our microbiota-dependent ATF6-driven and lipid-specific ATF6-driven gene signatures with decreased disease-free survival in CRC patients since primary therapy. Moreover, ATF6 activity correlates with the presence of CRC-associated bacteria in TCGA samples. Tumor-susceptible mice show alterations in lipid metabolites, particularly long-chain fatty acids (FA) and elongation of saturated FA. PICRUSt2 revealed bacterial lipid detoxification mechanisms, with an increased total abundance of oleate hydratase-positive species. Conclusion: Chronic ATF6-signalling alters host lipid metabolism and the lipid milieu in tumor-developing nATF6 IEC mice. ATF6-driven microbiota changes are concomitant with bacterial lipid detoxification mechanisms in the tumor niche. We postulate that chronic ATF6 signalling represents a clinically relevant pathologic response that alters the intestinal lipid milieu and thus selects for a tumor-promoting microbiota.